Trust and Quality of Communication with the Marriage Commitment of TNI AU Undergoing Long Distance Marriage - Ulviani, Tri; Nurfarhanah; Hariko, Rezki (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Couples who are in a long-distance marriage need a strong commitment to maintain their marriage. Challenges that often arise include feelings of anxiety, partner support, sharing of time, the temptation of infidelity, and the role of raising children. Trust, as confidence and concern for a partner, as well as good communication quality, are important factors that influence marital commitment in this situation. This research aims to analyze the relationship of trust and Communication quality and long distance marriage commitment. This research uses a quantitative descriptive approach with correlational quantitative methods. The research populations are totaling 60 pairs and a sample of 44 pairs. Sampling used purposive sampling technique. Data analysis is using descriptive statistical techniques, and then using multiple regression analysis. The findings of this research are: 1) the trust of married couples undergoing long distance marriages is in the high category at 48.86% (R2 = 0.632), 2) the communication quality of married couples undergoing long distance marriages is in the high category at 50.00% (R2 = 0.723), 3) the marital commitment of husband and wife couples undergoing long distance marriage is in the very high category at 56.82%, 4) there is a significant relationship between trust and quality of communication with the Indonesian Air Force's long distance marriage commitment through the test The significance of the correlation coefficient is R Square = 0.757 with a very strong level of correlation.